Prosthodontic Treatment With Implant Fixed Prosthesis for a Patient With Ectodermal Dysplasia: A Clinical Report - Behnoush Rashedi, DMD, MSEd, MS (Journal of Prosthodontics, 2003)
Oral characteristics of ectodermal dysplasia (ED) include hypodontia or anodontia of the primary or permanent teeth, impacted teeth, malformed and widely spaced peg-like teeth, and underdeveloped alveolar ridges